Teachers' Ability to Develop Mathematics Teaching Modules: Study of the Implementation of the Independent Curriculum in Pontianak City - Yulis Jamiah; Marianus Hengki; Siregar, Nurfadilah; Nadya Febriani Meldi (Department of Mathematics Education Program IPI Garut, 2024)
Penelitian ini bertujuan untuk mengukur kemampuan guru matematika SMP/SMA/SMK di Pontianak dalam mengembangkan perangkat pembelajaran berdasarkan Kurikulum Merdeka. Tujuan spesifiknya adalah: 1) mendeskripsikan kemampuan guru dalam menjabarkan kriteria perangkat pembelajaran Kurikulum Merdeka, dan 2) mendeskripsikan kemampuan guru dalam menjabarkan komponen perangkat pembelajaran Kurikulum Merdeka. Penelitian ini mencakup beberapa tahap: analisis teori kemampuan guru, eksplorasi karakteristik perangkat pembelajaran, identifikasi masalah, kajian perangkat pembelajaran hasil pengembangan guru, serta pengumpulan data melalui angket, wawancara, dan observasi. Metode yang digunakan adalah metode deskriptif dengan analisis data kualitatif dan kuantitatif. Hasil penelitian menunjukkan bahwa kemampuan guru dalam mengembangkan perangkat pembelajaran, khususnya dalam menjabarkan tiga komponen dan empat kriteria perangkat pembelajaran Kurikulum Merdeka, berada pada kategori baik. Namun, kemampuan dalam menjabarkan item setiap komponen dan kriteria perangkat pembelajaran berada pada kategori cukup baik.This study aims to assess the abilities of junior high, senior high, and vocational school mathematics teachers in Pontianak in developing learning tools based on the Merdeka Curriculum. Specifically, it seeks to: 1) describe teachers' abilities in detailing the criteria for Merdeka Curriculum learning tools, and 2) describe teachers' abilities in detailing the components of Merdeka Curriculum learning tools. The study includes several stages: theoretical analysis of teachers' abilities, exploration of learning tool characteristics, problem identification, review of learning tools developed by teachers, and data collection through questionnaires, interviews, and observations. The research employs a descriptive method with both qualitative and quantitative data analysis. Results indicate that teachers' abilities in developing learning tools, particularly in detailing three components and four criteria of the Merdeka Curriculum learning tools, are categorized as good. However, their ability to detail each item of the components and criteria is categorized as fair good.